Potential and Constraints of Cultural Tourism in Sade Village: An Analysis of Social, Cultural, and Economic Impacts - Dewa Ayu Abhinandati Prajna Pratisthita; Bella Charrollina; Angelita Peridibua Mudamakin; Indrawan Wiratama; I Ketut Surata; I Putu Utama (Indonesian Journal of Banking and Financial Technology, 2025)
This study examines the potential and challenges in tourism development in Sade Village, a cultural village in Lombok that is famous for its Sasak traditions and culture. This study aims to understand how tourism affects local communities from social, cultural, and economic aspects, and to identify barriers that hinder the progress of sustainable tourism in the village. In-depth analysis shows that, although tourism provides significant economic benefits, there are still major challenges related to cultural preservation, infrastructure improvement, and community skill enhancement in dealing with tourists. The findings of this study are expected to be the basis for formulating a more effective and sustainable tourism development strategy in Sade Village.